Culturally-Based Education: FAST Animation Video in the Banjar Language to Increase Family Awareness in Stroke Detection - Wibawa, Nurhalisa; Aridamayanti, Bernadetta Germia; Arif, Rifda Nur Achriyana; Herawati (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2025)
Stroke is a leading cause of death and disability worldwide, including in Indonesia. Low public awareness in recognizing stroke symptoms is a major factor contributing to delayed treatment. This study aims to analyze the effectiveness of culture-based education using a Banjar-language FAST animation video in improving family knowledge and attitudes toward early stroke detection. The research design used a quasi-experimental method with a pre-test and post-test as well as a control group. The sample consisted of 100 respondents divided into intervention and control groups. The results showed a significant increase in knowledge and attitude scores in the intervention group (p < 0.05). This indicates that culture-based education is more effective than conventional education. In conclusion, this approach can serve as a more inclusive health education model for communities with language limitations.